Electrical and Electrochemical Monitoring of Nucleic Acid Amplification - Goda, Tatsuro; Tabata, Miyuki; Miyahara, Yuji (Frontiers in Bioengineering and Biotechnology, 2015)
Nucleic acid amplification is a gold standard technique for analyzing a tiny amount of nucleotides in molecular biology, clinical diagnostics, food safety, and environmental testing. Electrical and electrochemical monitoring of the amplification process draws attention over conventional optical methods because of the amenability toward point-of-care applications as there is a growing demand for nucleic acid sensing in situations outside the laboratory. A number of electrical and electrochemical techniques coupled with various amplification methods including isothermal amplification have been reported in the last ten years. In this review, we highlights recent developments in the electrical and electrochemical monitoring of nucleic acid amplification.